Identification of a novel heterozygous missense TP63 variant in a Chinese pedigree with split-hand/foot malformation - Mingzhu Miao; Shoulian Lu; Xiao Sun; Meng Zhao; Jue Wang; Xiaotan Su; Bai Jin; Lizhou Sun (BMC, 2022)
Abstract Background Tumor protein p63 is an important transcription factor regulating epithelial morphogenesis. Variants associated with the TP63 gene are known to cause multiple disorders. In this study, we determined the genetic cause of split-hand/foot malformation in a Chinese pedigree. Methods For this study, we have recruited a Chinese family and collected samples from affected and normal individuals of the family (three affected and two normal). Whole exome sequencing was performed to detect the underlying genetic defect in this family. The potential variant was validated using the Sanger sequencing approach. Results Using whole-exome and Sanger sequencing, we identified a novel heterozygous pathogenic missense variant in TP63 (NM_003722.5: c.921G > T; p.Met307Ile). This variant resulted in the substitution of methionine with isoleucine. Structural analysis suggested a resulting change in the structure of a key functional domain of the p63 protein. Conclusion This novel missense variant expands the TP63 variant spectrum and provides a basis for genetic counseling and prenatal diagnosis of families with split-hand/foot malformation or other TP63-related diseases.